Paweł Churski (red.) Contemporary problems of regional development and regional policy. Quaestiones Geographicae,vol. 29,2. - Czasopisma, Redakcja (Rozwój Regionalny i Polityka Regionalna, 2010)
Paweł Churski (red.) Contemporary problems of regional development and regional policy. Quaestiones Geographicae,vol. 29,2. Wydawnictwo Naukowe UAM, Poznań 2010, 106 ss. ISBN: 978-83-232-2168-5